Questions of Communicative Change and Continuity In Memory of Wolfram Peiser - Krämer, Benjamin; Müller, Philipp (Nomos Verlagsgesellschaft mbH & Co. KG, 2022)
Faced with the ongoing evolution of the media landscape, media and communication science is constant-ly asking itself new questions concerning the tension between stability and change in social communication. In this context, many relevant topics exist for which there are still no publications that would systematically evaluate what we know (empirically and non-empirically) so far and what conclusions can be drawn from existing knowledge. This volume aims to provide systematic answers to important current or continually relevant questions in the field, with contributions that are entirely focused on a specific question, thus leaving room for thorough arguments. The volume is dedicated to the memory of Professor Wolfram Peiser. With contributions by Hans-Bernd Brosius, Felix Frey, Romy Fröhlich, Christina Holtz-Bacha, Benjamin Krämer, Philipp Müller, Christoph Neuberger, Carsten Reinemann, Anna-Luisa Sacher, Johanna Schindler, Klaus Schönbach and Cornelia Wallner.